AUDIT TATA KELOLA TEKNOLOGI INFORMASI COBIT 5 MANAJEMEN RISIKO - M Yasmin Ramadhan M; M Irwan Padli Nasution; Triase (Jurnal Sistem Informasi Kaputama (JSIK), 2022)
Conducting Information technology governance audits, which means conducting periodic checks on a system that has been built, now many audit models are emerging, but COBIT 5 is one of the relevant governance audits to use. The development of information systems goes hand in hand with the audit system, starting from reading a possible risk that will occur and preventing these risks, then in periodic checks can build a new innovation from the audit results itself, the lack of an information system is indeed a weakness of the system running, but with the evaluation, it means that the weaknesses of the system are minimized. This study discusses how to carry out risk management in an ongoing system with the APO12 domain on COBIT 5.